2021
DOI: 10.3897/folmed.63.e55346
|View full text |Cite
|
Sign up to set email alerts
|

A pilot study reveals the potential of miR-31-3p and miR-196a-5p as non-invasive biomarkers in advanced laryngeal cancer

Abstract: Introduction: Recently, miRNAs have become popular molecules used as non-invasive biomarkers in cancer diseases. Aim: The aim of the study was to explore the expression of four miRNAs isoforms: miR-31-3p, miR-196a-5p, miR-210-3p and miR-424-5p in plasma and tissue samples from patients with advanced laryngeal squamous cell carcinoma (LSCC) and healthy controls. Materials and methods: Fresh-frozen tumour and normal laryngeal tissue as well as plasma samples were obtained from 22 patients dia… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
5
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 8 publications
(5 citation statements)
references
References 35 publications
0
5
0
Order By: Relevance
“…The utility of miR-31 as a biomarker is further explored in several studies which suggest that, in various HNSCC patient sample types (saliva, plasma, tumor tissues), the expression levels of miR-31 increase and are positively correlated with poor pathological parameters [ 147 , 153 ] and advanced staging [ 155 ]. MiR-31 quantification could also serve as a useful marker of post-operative follow-up of OSCC, as salivary levels appear to be remarkably reduced after the excision of the oral carcinoma [ 154 ].…”
Section: The Role Of the Most Common Mirnas In Hncmentioning
confidence: 99%
“…The utility of miR-31 as a biomarker is further explored in several studies which suggest that, in various HNSCC patient sample types (saliva, plasma, tumor tissues), the expression levels of miR-31 increase and are positively correlated with poor pathological parameters [ 147 , 153 ] and advanced staging [ 155 ]. MiR-31 quantification could also serve as a useful marker of post-operative follow-up of OSCC, as salivary levels appear to be remarkably reduced after the excision of the oral carcinoma [ 154 ].…”
Section: The Role Of the Most Common Mirnas In Hncmentioning
confidence: 99%
“…Of those, 166 were excluded for describing HNSCC cases without focus on the larynx ( n = 28), for being exclusively in vitro studies ( n = 39), for having a number of patients less than 10 or for using patient data from public databases ( n = 50), for not quantifying miRNAs in patient samples ( n = 43) and for other reasons, such as for not having statistically significant results or wrong miRNA sequence ( n = 6). Finally, the review was performed on a total of 177 studies [ 22 , 23 , 24 , 25 , 26 , 27 , 28 , 29 , 30 , 31 , 32 , 33 , 34 , 35 , 36 , 37 , 38 , 39 , 40 , 41 , 42 , 43 , 44 , 45 , 46 , 47 , 48 , 49 , 50 , 51 , 52 , 53 , 54 , 55 , 56 , 57 , 58 , 59 , 60 , 61 , 62 , 63 , 64 , 65 , 66 , 67 , 68 , 69 , 70 , 71 …”
Section: Resultsmentioning
confidence: 99%
“…miR-31 is highly expressed, especially in SqCC, and its expression is a potential marker of metastasis or poor prognosis [ 37 ]. Previous studies have revealed that the expression levels of miR-31 are increased in various HNSCC samples (saliva, plasma, and tumor tissues) and are positively correlated with poor pathological parameters [ 38 , 39 ] and advanced staging [ 40 ]. miR-203 and miR-205 are well-known tumor suppressors in HNSCC.…”
Section: Discussionmentioning
confidence: 99%